Hubungan Pelayanan Informasi Obat Dengan Tingkat Kepatuhan Pasien Hipertensi Di UPT Puskesmas Sei Semayang Kec. Sunggal, Deli Serdang - Mafe Robbi Simanjuntak; Oscar Gilbert Surbakti; Disti Amanda Putri (STIKES Columbia Asia Medan, 2026)
Hypertension is a chronic non-communicable disease requiring long-term pharmacological therapy, and medication adherence remains a critical determinant of treatment success. Drug Information Services (DIS) delivered by pharmaceutical personnel at primary healthcare facilities are expected to enhance patients' knowledge, motivation, and adherence to antihypertensive therapy. This study aimed to analyze the relationship between Drug Information Services and medication adherence among hypertensive patients at UPT Puskesmas Sei Semayang, Sunggal District, Deli Serdang Regency. The research applied an analytical observational design with a cross-sectional approach. The population consisted of 300 hypertensive patients, from which 30 respondents were selected using simple random sampling. Data were collected using a validated 16-item Drug Information Service questionnaire and the Morisky Medication Adherence Scale-8 (MMAS-8), and were analyzed with the Spearman Rank Correlation test at a 95% confidence level. The results showed that 76.7% of respondents perceived DIS as good and 23.3% as poor, while adherence was categorized as moderate (46.7%), low (33.3%), and high (20.0%). The Spearman correlation revealed r = 0.118 and p-value = 0.534 (p > 0.05), indicating no statistically significant relationship between DIS and medication adherence. The findings imply that adherence in primary care is influenced by multiple factors beyond DIS alone, underscoring the need for multifactorial and structured pharmaceutical care interventions.